2018
DOI: 10.1080/14760584.2018.1510326
|View full text |Cite
|
Sign up to set email alerts
|

Recent development of enterovirus A vaccine candidates for the prevention of hand, foot, and mouth disease

Abstract: Hand, foot, and mouth disease (HFMD) is a childhood illness commonly caused by enterovirus A. Enterovirus A71 (EV-A71) and coxsackievirus A16 (CV-A16) are the most commonly identified viruses associated with HFMD. Recently, outbreaks caused by different enterovirus A including CV-A6 and CV-A10 are increasing. Being available now to protect against EV-A71 infection, inactivated EV-A71 vaccines cannot prevent coxsackievirus infections, thus limiting their general application in controlling HFMD. Multivalent HFMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 101 publications
1
33
0
Order By: Relevance
“…Collectively, these data expand our knowledge about immunogenicity elicited as a consequence of EV-A71 vaccination and natural infection. Coxsackievirus vaccine development has not gone beyond animal experiments; thus, no similar data exist for CVA6, CVA10, or CVA16 (15,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data expand our knowledge about immunogenicity elicited as a consequence of EV-A71 vaccination and natural infection. Coxsackievirus vaccine development has not gone beyond animal experiments; thus, no similar data exist for CVA6, CVA10, or CVA16 (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…Because the viruses causing HFMD are diverse, ongoing efforts exist to develop multivalent vaccines, especially those including antigens of the aforementioned common serotypes (15). Results from these preclinical studies using animal models showed a lack of cross-reactivity among EV-A71, CVA6, CVA10, and CVA16 (16,17).…”
mentioning
confidence: 99%
“…Several EV‐A71 vaccine candidates have been investigated in animal models, such as recombinant viral proteins, virus‐like particles and DNA vaccines, peptide vaccines, live attenuated vaccines, and formalin‐inactivated whole virus vaccines . Several review papers have delved into the advantages and disadvantages of these vaccine candidates . Knowledge of immune responses and epitopes has been applied in vaccine development.…”
Section: Prevention and Control: How Close We Are To Success?mentioning
confidence: 99%
“…A few major epitopes have been identified in immunized rabbits [66][67][68] and mice 67,69 (Table 1). In VP1, the mapped regions are the N-terminal (amino acids 1-100), 66,73 amino acids 208-220 of the GH loop (also known as SP70/VP1-43), 67,69 and amino acids [163][164][165][166][167][168][169][170][171][172][173][174][175][176][177] of the EF loop (also known as SP55). 69 Moreover, passive transfer of mouse anti-SP70 antiserum protected 80% of suckling Balb/c mice against lethal EV-A71 infectivity.…”
Section: Protective Humoral Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation